The kill list [large type] - Forsyth, Frederick, 1938- (Thorndike Press large print basic, 2014)
When a terrorist known as the Preacher targets for assassination a retired Marine general, whose son is TOSA's top hunter of men, the terrorist becomes the hunted -- landing him at the top of TOSA's Kill List.